2018
DOI: 10.3322/caac.21448
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in Lynch syndrome and other familial colorectal cancer syndromes

Abstract: The current understanding of familial colorectal cancer was limited to descriptions of affected pedigrees until the early 1990s. A series of landscape-altering discoveries revealed that there were distinct forms of familial cancer, and most were related to genes previously not known to be involved in human disease. This review largely focuses on advances in our understanding of Lynch syndrome because of the unique relationship of this disease to defective DNA mismatch repair and the clinical implications this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 160 publications
(297 reference statements)
3
115
0
4
Order By: Relevance
“…However, NGS studies have reported that as much as ~18% of patients diagnosed with CRC < age of 50 years have pathogenic variants in genes that are not traditionally associated with CRC ( ATM , CHEK2 , BRCA1 , BRCA2 , CDKN2A and PALB2 ) . Notably, there is a need to determine whether these variants contribute to hereditary CRC risk via the combination of low‐ and moderate‐penetrance susceptibility alleles …”
Section: Genetic Profile For Hereditary Crc: Lynch Syndromementioning
confidence: 99%
“…However, NGS studies have reported that as much as ~18% of patients diagnosed with CRC < age of 50 years have pathogenic variants in genes that are not traditionally associated with CRC ( ATM , CHEK2 , BRCA1 , BRCA2 , CDKN2A and PALB2 ) . Notably, there is a need to determine whether these variants contribute to hereditary CRC risk via the combination of low‐ and moderate‐penetrance susceptibility alleles …”
Section: Genetic Profile For Hereditary Crc: Lynch Syndromementioning
confidence: 99%
“…The guidelines from the American College of Medical Genetics and Genomics guide the process of sequence variant classification using criteria informed by expert opinion and empirical data [40]. The guidelines from the National Comprehensive Cancer Network for LS use modified Bethesda criteria that take into account young age of onset and tumor screening to address low penetrance of germline pathogenic variants [41]. …”
Section: Aim 1: Assessing the Challenges And Opportunities Of Implemementioning
confidence: 99%
“…Universal tumor testing is cost-effective and sensitive for LS screening in individuals with colorectal and endometrial cancers [42, 43]. Using clinical prediction models is also cost-effective for individuals with or without cancer [41]. …”
Section: Aim 1: Assessing the Challenges And Opportunities Of Implemementioning
confidence: 99%
“…The majority of cases in this subset are characterized by hypermethylation of the MLH1 promoter, which is also observed in approximately 15% of sporadic CRC cases [4,5]. Variants in the BRAF oncogene are able to distinguish LS from sporadic MMRde cient CRC; this has been demonstrated to be a powerful method for screening patients with LS [6,7]. A subset of patients with CRC, who manifest the MMR de ciency but have no identi ed germline variant in either MMR genes or the BRAF gene (absence of MLH1 methylation), have been de ned as having Lynchlike syndrome (LLS) [1,3,8].…”
Section: Introductionmentioning
confidence: 99%